(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Developmental information disseminated by NGOs through various channels is an indispensable resource of rural communities. Informal channels are effectively functioning intentionally or unintentionally between NGOs and the rural communities, through which developmental information is distributed. In this study an analysis is done on the types of informal sources through which developmental information is disseminated among the rural community. The efficiency of different informal channels in reaching out information to the people is measured.